Pengaruh Persepsi Harga, Brand Image, dan Electronic Word Of Mouth (E-Wom) terhadap Keputusan Pembelian (Studi Pada Konsumen Emina Cosmetics di Kota Semarang) - Araafiona Chandra Kusuma; Sari Listyorini; Sudharto P Hadi (Jurnal Ilmu Administrasi Bisnis, 2022)
The tight competition in the cosmetic industry caused Emina Cosmetics sales in 2019-2020 to decline. Especially in make-up products that experienced the most significant decline. Price perception, brand image, and e-WOM are suspected as factors that can influence purchasing decisions. This study aims to determine the effect of price perception, brand image and electronic word of mouth on purchasing decisions of Emina Cosmetics in Semarang City. This type of research is explanatory research with sampling technique using non-probability sampling technique and purposive sampling method. Collecting data using a questionnaire via google form. The sample in this study amounted to 100 consumers of Emina Cosmetics in the city of Semarang. This study uses the help of Microsoft Excel and SPSS for windows version 25.0 to test the validity, reliability test, correlation coefficient test, coefficient of determination, simple and multiple regression analysis, then test significance (t test and F test). The results of this study indicate that the price perception variable (X1), the brand image variable (X2) and the electronic word of mouth variable (X3) can simultaneously have a significant, strong and positive influence on the purchasing decision variable (Y). Simultaneous calculation of price perception has the greatest influence on purchasing decisions. Partially, price perception contributes 44.1% to purchasing decisions, brand image contributes 39.9% to purchasing decisions, while electronic word of mouth contributes 38.7% to purchase decisions. Then simultaneously price perception, brand image, and electronic word of mouth contributed 54.8% to purchasing decisions. It is recommended that Emina Cosmetics provide good quality at affordable prices. Next, innovate to develop and improve the product's brand image. Finally, Emina also needs to improve a fast response to negative reviews from consumers.